Caribbean Veneer Company - Bornás Huerta, Rafael V. (1993)
Case study of a small company founded in 1987 by «amateur" entrepreneurs who entrusted their management to operational executives used to «command done» without considering the importance of a plan and without basic technical information. The objective is to apply operational research to a production process of a company seeking to establish a level of input-process-product combination that maximizes the company's income or profit and /or minimizes its operating costs. Simple and easily interpreted mathematical models are used. The case claims the importance of guiding the production manager towards basic analytical information that allows him to identify the current state of the company and its resources in order to make technically feasible and economically profitable decisions. It shows that the application of the operational investigation does not imply the modification of the installed capacity of the company; on the contrary, their solutions correct the greater or lesser use of that capacity, bringing the input-output relationship closer to the maximum usable, which implies greater profits.